Zionism - Engel, David 1951- (Routledge, 2013)
Zionism is an international political movement that was originally dedicated to the resettlement of Jewish people in the Promised Land, and is now synonymous with support for the modern state of Israel. This addition to the Short Histories of Big Ideas series looks at the controversial and topical notion of Zionism from a balanced viewpoint, concentrating on where it came from, how it accomplished its goals, and why it affected so many people.
Firstitle pageblished 2009 by Pearson Education Limited
Includes bibliographical references and index
Keywords: Zionism / Israel; Zionism / History; Zionism; Electronic books